Comparing the Behavioral Patterns and Psychological Characteristics of Web Board Gamers and Gamblers - Han, Jiwon (Psychiatry Investig, 2018)
OBJECTIVE: In Korea, online board games, such as “flower cards,” are played using virtual money. In contrast, Internet-based gambling (ibGambling) concerns the use of real money to gamble online. We hypothesized that online board gamers using virtual money show less risky behaviors than do gamblers who use real money, and that, in regard to psychological aspects, online board gamers are less depressed and more introverted than online gamblers are. METHODS: For this study, 100 online board gamers, 100 ibGamblers, 100 offline gamblers (offGamblers), and 100 age- and sex-matched healthy controls were recruited by an online research company. Gambling behavior and self-efficacy were assessed using the Korean Gambling Behavior Scale-high/low factors (KGBS-H/L) and the Gambling Abstinence Self-efficacy Scale (GASS). Additionally, introversion, depression, and mania tendency were assessed. RESULTS: Online board gamers had good intentions gaming, as evidenced by their higher KGBS-L scores than ibGamblers and offGamblers, and they showed less risky behaviors, as evidenced by their lower KGBS-H scores than offGamblers. Additionally, online board gamers were less introverted than ibGamblers and less depressed than offGamblers. CONCLUSION: Online board gaming could be a gateway to the world of gambling (ibGambling or OffGambling). However, the higher tendency of online board gamers to engage in good intentioned gaming could help prevent online board gaming from progressing to online or offline gambling.